4R nutrient stewardship and nitrous oxide losses. Issue 1 (1st February 2018) - Flis, Sally
Abstract : Nitrous oxide (N2 O) is a potent greenhouse gas that can result in nitrogen loss from the soil. The scientific literature is deficient in studies that measure N2 O emissions, NO3 leaching, and crop performance across multiple sources of nitrogen fertilizer and changes in field practices. However, there are tools and strategies available to consultants and producers to improve nitrogen use efficiency and reduce N2 O emissions while not decreasing yield. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/543